Regional income disparities in Indonesia: Insights from the Williamson index and panel data analysis - Rachmawati, Linda Nur; Lubis, Firsty Ramadhona Amalia; Azzakiyyah, Nurul Azizah (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Indonesia records the highest income disparity in Southeast Asia and ranks sixth globally in terms of income inequality, as evidenced by its position in recent international analyses and inequality reports. This study aims to examine the effects of Gross Regional Domestic Product (GRDP) per capita, Human Development Index (HDI), Open Unemployment Rate (OUR), and investment on income distribution inequality, measured using the Williamson Index in Indonesia. The research utilizes panel data spanning from 2018 to 2022 across 34 provinces. A multiple linear regression analysis with panel data methodology was employed, selecting the Fixed Effect Model (FEM) as the most suitable estimator.​ The findings reveal that, collectively, all independent variables in the model significantly influence income distribution inequality. Individually, GRDP per capita has a positive and significant effect on income inequality, HDI exhibits a negative and significant impact, OUR shows no significant effect, while investment negatively and significantly affects income distribution inequality. ​This study contributes by providing input to stakeholders in formulating policies that can be implemented to address income distribution inequality, particularly in the Indonesia.